Identifying and Engineering Genes for Parthenogenesis in Plants - Vijverberg, Kitty; Ozias-Akins, Peggy; Schranz, M. Eric (Frontiers in Plant Science, 2019)
Parthenogenesis is the spontaneous development of an embryo from an unfertilized egg cell. It naturally occurs in a variety of plant and animal species. In plants, parthenogenesis usually is found in combination with apomeiosis (the omission of meiosis) and pseudogamous or autonomous (with or without central cell fertilization) endosperm formation, together known as apomixis (clonal seed production). The initiation of embryogenesis in vivo and in vitro has high potential in plant breeding methods, particularly for the instant production of homozygous lines from haploid gametes (doubled haploids, DHs), the maintenance of vigorous F1-hybrids through clonal seed production after combining it with apomeiosis, reverse breeding approaches, and for linking diploid and polyploid gene pools. Because of this large interest, efforts to identify gene(s) for parthenogenesis from natural apomicts have been undertaken by using map-based cloning strategies and comparative gene expression studies. In addition, engineering parthenogenesis in sexual model species has been investigated via mutagenesis and gain-of-function strategies. These efforts have started to pay off, particularly by the isolation of the PsASGR-BabyBoom-Like from Pennisetum, a gene proven to be transferable to and functional in sexual pearl millet, rice and maize. This review aims to summarize the current knowledge on parthenogenesis, the possible gene candidates also outside the grasses, and the use of these genes in plant breeding protocols. It shows that parthenogenesis is able to inherit and function independently from apomeiosis and endosperm formation, is expressed and active in the egg cell, and can induce embryogenesis in polyploid as well as haploid egg cells in plants. It also emphasizes the importance of functional endosperm to allow for successful embryo growth and viable seed production.